Organizational and environmental determinants of ballistics imaging productivity in United States crime laboratories - King, William R. (Journal of crime and justice, 2018)
This study employs a structural contingency theory framework to assess the influence of the formal organizational structure of crime laboratories and their environments, on the productivity of labs’ ballistics imaging systems. We contribute to the nascent evolution of organizational focus in forensics while exploring different ways in which overall lab performance can be conceptualized. We analyze data provided by the Bureau of Alcohol, Tobacco, Firearms and Explosives’ (ATF) National Integrated Ballistics Information Network (NIBIN), and data from the Bureau of Justice Statistics, Census of Publicly Funded Forensic Crime Laboratories, 2009. Three Negative Binomial models regressed the organizational and environmental variables on the productivity of crime labs, operationalized as their ability to produce bullet, brass, and total hits. Results indicate that in addition to the number of bullet and brass inputs, local labs are more productive in identifying ballistics imaging hits. Additionally, larger labs with a greater proportion of firearms requests and the ability to process those requests produce more hits. Although the current research did not find that organizational structure significantly predicted labs’ productivity, the importance of the population of bullet and brass inputs was clearly evident. Additionally, jurisdiction plays a vital role in the production of hits.